Buoyancy-Engine Endurance Test by Use of Hydraulic Test Device - Chong-Moo Lee; Chan Jong Park; Cheol Su Park; Jong-Jin Par (한국해양공학회지)
Buoyancy engines used in underwater gliders require durability due to repeated operation over months. Using a hyperbaric chamber for durability testing is not only expensive but also challenging to operate, as the chamber require continuous monitoring for several days. In our laboratory, we develop a hydrostatic test device that allows us to test a buoyancy engine in open air to verify its durability. The hydrostatic test device allows us to observe problems associated with the buoyancy engine, which is repeatedly exposed to high-pressure environments in the laboratory, and to verify its durability via repeated operation under varying environmental pressures, which mimics the actual situation. The hydrostatic test achieves more than 1,000 cycles, which is equivalent to three months of operation of an underwater glider. As the power source used in this case is a battery, the amount of power consumed is measured to ensure that it is within the capacity of the battery used. The result shows that it is within the acceptable range.